Interview with Eric Rouleau. TURKEY HAS BEEN GIVEN ITS CHANCE TO ENTER THE EUROPEAN UNION: This interview was conducted by Jean Catsiapis - Rouleau, Eric; Catsiapis, Jean (Études helléniques / Hellenic Studies, 2000)
--